Monitoring of glulam structures by theodolite intersection - Price, W.F. (2002)
The use of glued laminated timber (glulam) in building and construction provides a designer with an attractive, environmentally friendly alternative to steel and concrete. However, along with other engineering materials, glulam is subject to creep and in order to use it efficiently without the risk of unacceptable long-term deflections occurring, a reliable method of estimating creep in glulam is desirable.